Fuller's earth (bentonite) in the Lower Cretaceous (Upper Aptian) of Shanklin (Isle of Wight, southern England) (Geological Society Publishing House, 2002)
A 35 cm fuller's earth (bentonite) bed is recorded from the Upper Aptian (Lower Cretaceous) Ferruginous Sands Formation (Lower Greensand Group), southwest of Shanklin, Isle of Wight. The stratigraphic location and sedimentological context of the bed are described: the host succession is cyclical, containing evidence of non-deposition, faunal colonization and current reworking of sediments. Mineralogical and petrographic analyses demonstrate the dominance of smectite (Ca-montmorillonite) and the presence of feldspar shards in the fuller's earth bed. Geochemical data indicate a close similarity to the fuller's earth beds formerly exposed at Redhill(Surrey), for which an intra-plate, trachytic volcanic source is suggested. The sedimentological, stratigraphic and volcanic implications of the discovery are discussed.